Differences in Self-Regulation of Male and Female Students in SMP N 2 Padang that Implement the Full Day School System - Mulyadi Firdaus; Indra Ibrahim (Jurnal Neo Konseling, 2019)
This research is motivated by the phenomenon of the number of students in a school who implement a full day school system that cannot regulate time either in learning or not, the number of students who often go out of class during class hours, and the number of students who are often late and more male students are found often do some of these things compared to female students. The purpose of this study was to examine the differences in self-regulation of male and female students in SMP N 2 Padang which implemented a full day school system. This research is a comparative descriptive study with quantitative methods. The total sample of 278 students was selected using the Proportional Random Sampling technique. The research instrument used was the student self-regulation questionnaire. Data were analyzed by descriptive statistical techniques and t-test (t test) techniques with the help of SPSS For Windows 20.0. The results revealed that (1) self-regulation of male students is in the high category (2) self-regulation of female students is in the high category, and (3) there is no significant difference between self-regulation of male and female students, obtained F is 0.398 with a significant 0.529 which means greater than 0.05, the value of t used is Equal variances assumed. The value of t obtained is -1.103 with probabilities (sig) 0.271> 0.05 then H0 is accepted.